Comptrollers. Cámara de Cuentas de la Comunidad de Madrid (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2008)
Summary: I. FUNCTIONS OF THE CÁMARA DE CUENTAS.—II. THE SCOPE OF THE CÁMARA DE CUENTAS ACTIVITY (COMPTROLLERS OFFICE).—III. ACCOUNTING FUNCTIONS.—IV. CONSULTING FUNCTIONS.—V. AUDIT PAPERS.—VI. ACCOUNTING RESPONSIBILITY. VII. ORGANIZATION.